PENGARUH PROBLEM-BASED LEARNING MULTIMEDIA DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Laksmi Evasufi Widi Fajari (LPPM Universitas Bina Bangsa, 2022)
This research aims to analyze the effect of the use of the PBL-based multimedia and learning motivation on the students’ critical-thinking skills in elementary school. This research method is quasi-experimental with the 2x2 factorial design. The sample in this research consisted of 62 students with 31 control-class students who taught with module and 31 experimental-class students who taught with problem-based learning multimedia with a total sampling technique. The data collection techniques were the open-ended critical-thinking skill test and learning motivation questionnaire. The data analysis technique used was a prerequisite test and research hypothesis test. The prerequisite tests include normality and homogeneity tests. The research hypothesis test used a Two-Way ANOVA with SPSS 25. The results of this research showed that: (1) there is the influence of multimedia-based PBL in the experiment class on students’ critical-thinking skills (the mean score of the experimental class is 69±2.890 and of the control class 51±3.071); (2) there is the influence of high and low learning motivation on the students’ critical-thinking skills (the mean score of the students with high motivation is 68.572 and those with low motivation 52.171); and (3) there is no interaction between the PBL-based multimedia and the learning motivation on the students’ critical-thinking skills